1995
DOI: 10.1093/treephys/15.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of phenolics in mycorrhizas of Larix decidua Mill.

Abstract: Soluble and cell-wall-bound phenolics in mycorrhizas of Larix decidua-Laccaria amethystea and in nonmycorrhizal fine roots of larch grown in sterile culture were analyzed by HPLC. The soluble phenolics p-hydroxybenzoylglucose, p-hydroxybenzoic acid glucoside, picein, catechin, and epicatechin were identified in nonmycorrhizal fine roots. The same phenolics also occurred in mycorrhizas, but only in very small quantities compared with those in nonmycorrhizal fine roots. The amount of cell-wall-bound ferulic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 14 publications
2
23
4
Order By: Relevance
“…Reduced catechin contents were found in roots of Fagus sylvatica L. and Larix decidua Mill. after colonisation by ectomycorrhizal fungi [46][47][48]. The reduced catechin concentrations in common buckwheat roots and increased rutin concentrations in tartary buckwheat roots seen after fungal colonisation in the present study indicate specific changes in the metabolic pathways related to fungal infections.…”
Section: Discussionmentioning
confidence: 49%
“…Reduced catechin contents were found in roots of Fagus sylvatica L. and Larix decidua Mill. after colonisation by ectomycorrhizal fungi [46][47][48]. The reduced catechin concentrations in common buckwheat roots and increased rutin concentrations in tartary buckwheat roots seen after fungal colonisation in the present study indicate specific changes in the metabolic pathways related to fungal infections.…”
Section: Discussionmentioning
confidence: 49%
“…In pine, a whole array of genes encoding enzymes of phenolic biosynthesis and polymerization, such as cinnamoyl-CoA reductase, cinnamoyl alcohol dehydrogenase, xyloglucan transendoglucanase, and peroxidase, were suppressed (Heller et al, 2008). Decreases in cell wall phenolics and peroxidase activities have previously been reported in mature conifer mycorrhizas (Mü nzenberger et al, 1995(Mü nzenberger et al, , 1997. In functional poplar EMs, the cells ensheathed by the Hartig net did not incorporate phenolic compounds, in contrast to the epidermal cells from which they were derived (Fig.…”
Section: Discussion Em Roots Display a Shift In The Phytohormone Balamentioning
confidence: 74%
“…Higher mycorrhizal infection in pine roots in expt 2 at lower N availability did not increase total phenolics concentration in roots. Mu$ nzenberger, Kottke & Oberwinkler (1995) found that phenolic concentration was reduced in fine roots of larch before mycorrhizal infection. On the other hand, Kainulainen et al (1996) found no correlation between natural mycorrhizal infection and total phenolic concentration in pine roots.…”
Section: Effects Of Mycorrhizas On Host Plant Qualitymentioning
confidence: 99%